O Incidente de Resolução de Demandas Repetitivas: perspectivas e aplicação - Silva, Cristina Menezes da (2021)
The present work aims to analyze the Repetitive Demand Resolution Incident as an unprecedented procedural technique conceived with the expectation of helping to combat the process crisis by which the Judiciary Branch. Created by the Code of Civil Procedure, within the new system of precedents, the IRDR proposes to honor the principles of legal security, isonomy and procedural celerity in dealing with repetitive litigation. This current and complex phenomenon, a consequence of the mass society in which we live, challenges new ways of thinking and implementing jurisdictional activity. The new mechanism was designed to allow the best and most rational management of repetitive demands, based on an alignment with constitutional precepts. Thus, the focus of the work will be analyzed if the IRDR is adequate and sufficient to achieve its objectives of contributing to a more adequate, stable and coherent legal order, adequate to the demands of contemporary society